The Influence of Work-Life Balance and Job Satisfaction on the Productivity of Generation Z Employees in Startup Companies - Budiman, Budiman (Sean Institute, 2025)
This study explores the influence of work-life balance and job satisfaction on the productivity of Generation Z employees in startup companies in Jakarta. The rapid growth of startups provides opportunities for innovation and flexible careers, yet it also creates challenges related to workload and employee well-being. A quantitative explanatory approach was applied, involving Generation Z employees working in Jakarta-based startups. Data were collected using a structured questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software. The findings show that both work-life balance and job satisfaction positively affect employee productivity, with job satisfaction emerging as the stronger determinant. Employees who feel satisfied with their job are more motivated and engaged, while those who experience balance between work and personal life are better able to maintain focus and well-being. The study suggests that enhancing job satisfaction and supporting work-life balance are essential strategies for sustaining productivity in startup environments.